Physiological and biochemical mechanisms of fruit cracking: A review - KAUR, RAVNEET; KAUR, NIRMALJIT; BAJYA, MAMTA; BAJAYA, TEJPAL (The Indian Journal of Agricultural Sciences, 2022)
Fruit cracking is a serious physiological disorder that affects fruit quality and productivity. It is a pre-harvest disorder that results in poor quality of fruits; these are not marketable and cause economic losses to growers. Generally, fruit cracking occurs during the second phase of fruit growth when expanding pulp induces pressure to peel and peel becomes thinner and microcracks appear, ultimately fruit splits and drops off from tree. Several factors that contribute to fruit cracking are irregular water supply, heavy crop load, warm-humid climatic conditions, nutrient mis-management and hormonal imbalance. Cultivars having thinner peels and deficiency of Ca, K, B and P in soils are more prone to fruit cracking. This review provides the physiological and biochemical basis of fruit cracking along with recommended control measures to reduce this disorder. Foliar application of synthetic auxins, gibberellins and minerals (Ca, Zn, P and B) at different time intervals for different species to significantly reduce fruit cracking is included in this review. Further molecular studies need to be proposed to study the actual mechanism of cracking through function of genesand biotechnological approaches can be followed so that cracking resistant varieties are produced